Acute changes in motor unit discharge property after concentric versus eccentric contraction exercise in knee extensor. (December 2022) - Hirono, Tetsuya; Kunugi, Shun; Yoshimura, Akane; Holobar, Aleš; Watanabe, Kohei
Abstract: This study aimed to investigate the motor unit firing property immediately after concentric or eccentric contraction exercise. Eighteen healthy men performed repetitive maximal isokinetic knee extension exercises with only concentric or eccentric contraction until they exerted less than 80% of the baseline strength. Before and after the fatiguing exercise, high-density surface electromyography of the vastus lateralis was recorded during submaximal ramp-up isometric contraction and individual motor units were identified. Only motor units that could be tracked before and after exercise were analyzed. Muscle cross-sectional area of the vastus lateralis was measured using ultrasound, and electrically evoked torque was recorded before and after the exercise. Sixty-five and fifty-three motor units were analyzed before and after the concentric and eccentric contractions, respectively. The results showed that motor units with moderate to high recruitment thresholds significantly decreased recruitment thresholds under both conditions, and the motor unit discharge rates significantly increased after concentric contraction compared to eccentric contraction. A greater muscle cross-sectional area was observed with concentric contraction. The evoked torque was significantly decreased under both conditions, but no difference between the conditions. These results suggest that fatiguing exercise with concentric contraction contributes to greater neural input to muscles and metabolic responses than eccentric contraction.